2017
DOI: 10.1016/j.respol.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Is there a first mover advantage in science? Pioneering behavior and scientific production in nanotechnology

Abstract: International audienceThis article investigates whether pioneers in a research field have a sustainable first mover advantage in publications. Combining bibliometric (publications, citations, co-authorship) with survey data on 495 nanotechnology researchers, we analyzed career attributes, professional context and production overtime. Our econometric estimates highlight two main results. First, pioneering behavior is not exogenous: it is more probable among scientists who are already established in their " moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 72 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…We found that the more quickly an article is recognized by scientific community, the more citations it is likely to receive. This effect is sometimes known as the "first mover advantage": being a pioneer leads to a strong advantage in scientific performance (Sabatier and Chollet 2017). The dynamic Waring model of Glänzel and Schubert (1995) also proved the influence of the number of early citations on those obtained later, which explains the cumulative advantage.…”
Section: Citation-related Factorsmentioning
confidence: 93%
“…We found that the more quickly an article is recognized by scientific community, the more citations it is likely to receive. This effect is sometimes known as the "first mover advantage": being a pioneer leads to a strong advantage in scientific performance (Sabatier and Chollet 2017). The dynamic Waring model of Glänzel and Schubert (1995) also proved the influence of the number of early citations on those obtained later, which explains the cumulative advantage.…”
Section: Citation-related Factorsmentioning
confidence: 93%
“…First-mover advantages and disadvantages have been studied in various realms, such as negotiations (Loschelder et al, 2016), corporate sustainability (Uşar et al, 2019), political science (O’Brien, 2017) and nanotechnology (Sabatier & Chollet, 2017). After the seminal work of Lieberman and Montgomery (1988) on first-movers using organizational strategy perspective, first-mover behavior has received a lot of attention in the strategic management scholarship.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It was found that first entrants had a positive market-share advantage over later entrants and the physical distribution drove most of the advantage. Sabatiera and Cholletb (2017) investigated whether pioneers in a research field had a sustainable first-mover advantage in publications. They combined bibliometric (publications, citations, co-authorship) with survey data and found that pioneering behavior was not exogenous, and even after controlling for the endogeneity of entry timing, they found a strong first-mover advantage.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%